2007
DOI: 10.1097/01.iae.0000256039.59142.22
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Macular Function by Focal Electroretinogram and Pattern Electroretinogram Before and After Epimacular Membrane Surgery

Abstract: In EMM eyes, the decrease in visual acuity is related to dysfunction of both preganglionic (abnormal fERG) and ganglionic (abnormal pERG) macular elements. Surgical removal of EMM may induce improvement of the function of both outer and innermost macular retinal layers, leading to a related increase in visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
(39 reference statements)
4
23
1
Order By: Relevance
“…21 There are few reports of evaluating postoperative visual outcomes of ERM surgery with PERG. Furthermore, as the previous study 22 did not conform to the International Society of Clinical Electrophysiology and Vision standard, the comparison with our results is very limited.…”
Section: Discussioncontrasting
confidence: 50%
“…21 There are few reports of evaluating postoperative visual outcomes of ERM surgery with PERG. Furthermore, as the previous study 22 did not conform to the International Society of Clinical Electrophysiology and Vision standard, the comparison with our results is very limited.…”
Section: Discussioncontrasting
confidence: 50%
“…Electrophysiological study of eyes with ERM have shown both inner and outer retinal dysfunction in eyes with vision loss from ERM. 7 On the other hand, we found a poor correlation between macular thickening and decrease in visual function as assessed by MP-1, highlighting again the fact that retinal thickening per se outside the fovea does not necessarily result in reduced visual function. Similarly, Arichika et al 17 recently found that the inner retinal thickening in the perifoveal region did not correlate with decrease in visual acuity.…”
Section: Discussionmentioning
confidence: 51%
“…[4][5][6] Multifocal ERG studies showed changes in both the inner and outer retinal layers associated with ERM leading to speculations that changes in both inner and outer retinal layers may account for the decrease in visual function associated with idiopathic ERM. 7 Fourier-domain OCT (FD-OCT) is a novel extension of OCT technology, in which the sample structure is measured in the form of spectral fringes and the inverse Fourier transformation is used to extract the depth scattering intensity profile (A-scan). 8 The parallel A-scan detection achieved with FD-OCT allows for a 100-fold higher data acquisition speed over time-domain (TD-OCT) without reduction in system sensitivity, leading to real time, in vivo imaging with fewer motion artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…3 Electrophysiologic studies have shown both outer and inner retinal layer dysfunction associated with vision loss in eyes with idiopathic ERM. 3,4 This report shows that an AO-flood fundus camera and Fd-OCT can be used to visualize subtle changes within the retinal layers in eyes with ERM. Disruptions or irregularities of the photoreceptor layer can occur, as shown by irregularities in the ONL on Fd-OCT.…”
Section: Discussionmentioning
confidence: 85%
“…2,3 Electrophysiologic studies have shown inner and outer retinal abnormalities associated with ERM, but these changes do not always correlate with visual acuity. 3,4 Vitrectomy surgery is commonly performed when visual disturbance is significant. However, despite surgical removal of the membrane, only up to 70% of eyes have significant improvement in vision, and macular profile on OCT rarely returns to normal after surgery.…”
mentioning
confidence: 99%